LEGISLATION FOR MOUNTAIN TRAILS AND PATHS AS A FACTOR FOR DEVELOPMENT OF MOUNTAINEERING TOURISM IN MACEDONIA - Reckoski, Risto (Horizons - International Scientific Journal, 2020)
The adoption of the Law on Mountain Trails from 2014, amended in 2015, gives hope that conditions for the development and promotion of mountaineering tourism will be created in Macedonia, by establishing safe conditions for using mountain and hiking trails and paths. The adoption of the Law determines the conditions and the arrangement of mountain trails and paths, their maintenance, classification and categorization, as well as other issues important for their use. In this way, greater protection of the nature and prevention of negative consequences for biodiversity will be achieved. This Law, together with Bylaws, contains numerous regulations that are fully related to the determination of the mountain paths and trails. The legislation is a good precondition for the development of this segment of alternative tourism in Macedonia.